Trust Requirements Approach For Eliciting Requirements Autonomous Car - Hakimi, Halimaton Saadiah (2020)
A new revolution of the automotive industry is hitting the industry with the need for an autonomous vehicle. This is in line with the Mega Science 3.0 Roadmap 2020-2050, which requires the industry 10 provide safer and more efficient driver-free driving. However, the acceptance level of the autonomous car s still minimal due to lack of trust in the autonomous technology. In this case, the challenging task for automakers are to gain user acceptance in using these highly technology cars, Although much effort has been made to grain user’s acceptance such as improving the safely features of the car, yet there have been very limited works to elicit trust able requirements of the cars before the development of an autonomous car. In this case, eliciting accurate functional requirements s challenging, especially for automotive engineers who are not well with the business process and the vocabulary used in the autonomous domain. Motivated by these problems, the objective of this thesis are three-folds; Firstly, to analyze trust requirements comprising trust attributes and trust properties, secondly to propose a new trust requirements approach in eliciting autonomous requirements, and thirdly to evaluate the usability of proposed trust requirements approach. This thesis proposes a new automated approach to assist the automotive engineer and client-stakeholders to elicit trust requirements of the autonomous car. For this, we started with an analysis of the significant trust attributes and trust properties of autonomous. Next, we have developed a trust requirements autonomous car (TREAC) pattern library in order to store all the input and significant trust attributes and trust properties of the autonomous car. Then, we embed the TReAC pattern library to the elicitation to elicit requirements of the autonomous car. Here, an automated tool support called Autocarreq. MEReq is also developed to realize the approach, Finally, a comprehensive evaluation of the approach, through usability test, was conducted, In summary, the finding of the evaluations show that our approach is useful and able eliciting trust requirements at the early stage of autonomous car development. It is believed that the proposed approach could help to increase the acceptance of users towards autonomous car. This is because the developments approach able to elicit and validate the trust level of the car requirements.